THE RESULT OF THE INITIATIVE: ROADS ARE BECOMING SAFE AND SMOOTH (International Conference on Economics, Finance, Banking and Management, 2025)
The atmosphere and landscape of the village, where you can watch the sunrise and sunset with pleasure, will increase your admiration